Quantum features of a charged particle in ionized plasma controlled by a time-dependent magnetic field - Choi, Jeong Ryeol; Maamache, Mustapha (Frontiers in Physics, 2014)
Quantum characteristics of a charged particle traveling under the influence of an external time-dependent magnetic field in ionized plasma are investigated using the invariant operator method. The Hamiltonian that gives the radial part of the classical equation of motion for the charged particle is dependent on time. The corresponding invariant operator that satisfies Liouville-von Neumann equation is constructed using fundamental relations. The exact radial wave functions are derived by taking advantage of the eigenstates of the invariant operator. Quantum properties of the system is studied using these wave functions. Especially, the time behavior of the radial component of the quantized energy is addressed in detail.